Prevalence of Vestibular Disorder in Older People Who Experience Dizziness - Chau, Allan T.; Menant, Jasmine C.; Hübner, Patrick P.; Lord, Stephen R.; Migliaccio, Americo A. (Frontiers in Neurology, 2015)
Dizziness and imbalance are clinically poorly defined terms, which affect ~30% of people over 65 years of age. In these people it is often difficult to define the primary cause of dizziness, as it can stem from cardiovascular, vestibular, psychological and neuromuscular causes. However, identification of the primary cause is vital in determining the most effective treatment strategy for a patient. Our aim was to accurately identify the prevalence of: Benign Paroxysmal Positional Vertigo (BPPV), peripheral, and central vestibular hypofunction in people aged over 50 years who had experienced dizziness within the past year. Seventy six participants aged 51 to 92 (mean ± SD = 69 ± 9.5 years) were tested using the Head Thrust Dynamic Visual Acuity (htDVA) test, Dizziness Handicap Inventory (DHI), as well as sinusoidal and unidirectional rotational chair testing, in order to obtain data for: htDVA score; DHI score; sinusoidal (whole-body, 0.1 - 2 Hz with peak-velocity at 30deg/s) Vestibulo-Ocular Reflex (VOR) gain and phase; transient (whole-body, acceleration at 150deg/s/s to a constant velocity rotation of 50deg/s) VOR gain and time constant; OptoKinetic Nystagmus (OKN) gain and time constant (whole-body, constant velocity rotation at 50deg/s). We found that BPPV, peripheral and central vestibular hypofunction were present in 38% and 1% of participants respectively, suggesting a likely vestibular cause of dizziness in these people. Of those with a likely vestibular cause, 63% had BPPV; a figure higher than previously reported in dizziness clinics of ~25%. Our results indicate that htDVA, sinusoidal (particularly 0.5 - 1 Hz) and transient VOR testing were the most effective at detecting people with BPPV or vestibular hypofunction, whereas DHI and OKN were effective at only detecting non-BPPV vestibular hypofunction.